Information System for the Registration of the Poor in Blang Bintang Subdistrict at the Blang Bintang District Office, Aceh Besar - Harmanda, Pandi (Journal Dekstop Application (JDA), 2023)
The process of data collection for the poor at the Blang Bintang Subdistrict Office has been computerized for some time; however, it still relies on Microsoft Excel, which leads to time inefficiencies and employee fatigue in conducting the data entry. This issue can result in delays in data management, subsequently affecting the timely distribution of various forms of assistance to the community. The aim of this study is to analyze and design an Information System for the Registration of the Poor in the Blang Bintang Subdistrict at the Blang Bintang District Office, Aceh Besar, using Microsoft Visual Basic 6.0. Data collection was carried out using several methods, including field studies and library research. The conclusion drawn from the analysis of the Information System for the Registration of the Poor is that the system will be used to process data for the poor at the Blang Bintang Subdistrict Office, Aceh Besar, enabling functionalities such as adding, editing, and searching for data. Additionally, the system will be equipped to generate reports, such as lists of beneficiaries, among others. This application is intended to serve as an alternative tool for processing the data of the poor at the Blang Bintang Subdistrict Office, Aceh Besar